Differential effects of chemotherapeutic drugs versus the MDM-2 antagonist Nutlin-3 on cell cycle progression and induction of apoptosis in SKW6.4 lymphoblastoid B-cells - Barbarotto, E.; Corallini, F.; Rimondi, E.; Fadda, R.; Mischiati, C.; Grill, V.; Vaccarezza, Mauro; Celeghini, C. (2008)
We have compared the cytotoxic/cytostatic responses of the SKW6.4 lymphoblastoid B-cells to the alkylating agent chlorambucil, the purine analog fludarabine, the non-genotoxic activator of the p53 pathway, Nutlin-3, used alone or in association with the death-inducing ligand recombinant TRAIL. Exposure to chlorambucil, fludarabine, and Nutlin-3 induced p53 accumulation and variably affected cell cycle progression in SKW6.4 lymphoblastoid cells. In particular, chlorambucil induced cell cycle accumulation at the G2/M checkpoint; Nutlin-3 induced early cell cycle arrest at the G1/S checkpoint, while fludarabine showed an intermediate behavior. On the other hand, recombinant TRAIL alone did not affect cell cycle progression but induced a rapid increase of apoptosis. Analysis of the gene expression profile of the p53-transcriptional targets showed distinct features between chlorambucil, Nutlin-3 and fludarabine, which likely account for their differential effect on cell cycle in SKW6.4 cells. In particular, chlorambucil upregulated the steady-state mRNA expression of SFN/14-3-3s, a gene involved in G2/M cell cycle arrest. Of note, all agonists upregulated TRAIL-R2 expression in SKW6.4 cells both at the mRNA and protein levels. Consistently, pretreatment with chlorambucil, fludarabine and Nutlin-3 enhanced SKW6.4 sensitivity to TRAIL-mediated apoptosis. © 2007 Wiley-Liss, Inc.